Ways to improve the methodical competence of teachers of physical education and special training - S.I. Glazunov (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The purpose of the study - to identify ways to improve the methodical competence of teachers of physical education and special training. It is established that an important component of professional competence of teachers is their methodical competence. Outlines the elements of methodical competence: knowledge, skills, competencies that effectively influence on students and methodically and intelligently implement educational and training goals. Found that the main directions of the formation and improvement of methodical competence of teachers is to actively participate in the activities of educational, methodical, scientific and professional work, training in the skills, self-education. It is shown that the main element of the restructuring of their own teaching activities in the educational environment is purposeful self teachers, which allows you to take them to the methodological creativity. Self-education should be seen as a necessary condition for the implementation of plans to improve the competence of teachers.